A proposal for a federalized unemployment insurance mechanism for Europe - Leila E. Davis; Charalampos Konstantinidis; Yorghos Tripodis (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
The ongoing crisis in the eurozone, together with growing evidence of structural imbalances, points to a role for new institutions to support a more stable European Monetary Union (EMU) structure. As is well established in the context of monetary union when business cycles are not synchronized, a system of fiscal transfers can support monetary union. Unemployment insurance (UI) is, in particular, a key component of fiscal crisis management. UI supports household incomes during downturns, and also acts as an automatic stabilizer, thereby helping individual countries respond to asymmetric shocks. This paper proposes a 'federalized' EMU-level UI mechanism as one program that can contribute to a system of fiscal transfers in the EMU, and estimates the cost of the proposed system under different financing and eligibility scenarios. We find that, under a variety of reasonable institutional parameters, such a system is fiscally feasible with limited reason to expect adverse employment effects in member countries. We conclude that fiscal transfers extended via automatic stabilizers are a productive avenue towards a more stable eurozone architecture.
Keywords: E45; E61; E62; 330; eurozone; unemployment insurance; fiscal transfers